Countering Islamophobia to Live in a Harmony in America After the 9/11 Attacks : A Religious Moderation Reflected in the Novel Yusuf Azeem is not a Hero (2021) - Dahlan, Dahlan (Jurnal Adabiyah, 2024)
This study discussed the portrayal of Islamophobia and how to encounter it to live in a harmony in America after the 9/11 Attacks in the novel Yusuf Azeem Is Not a Hero by Saadia Faruqi. This research aimed at examining how to encounter islamophobia in the aftermath of the 9/11 Attacks portrayed in the novel. This study applied the qualitative descriptive method to analyse the data and note-taking as the research instrument. This study is represented through the point of view of genetic structuralism of how the author as a Moslem delivers her experiences that takes place in the life of the author in facing the Islamophobia into a novel. This study finds how the main characters struggle to fight against the islamophobia and this study figures out the efforts of countering it until the Moslem are accepted in social community: showing exemplary moral attitudes and actions, Having a courage in facing challenging situations as an attempt to explain the real Islam, showing tolerance (religion moderation) and Love and the author voices these ways to approve to the public about the true face of Islam through a literary work. Abstrak Penelitian ini membahas tentang gambaran Islamofobia dan cara menghadapinya untuk hidup harmonis di Amerika pasca Serangan 9/11 dalam novel Yusuf Azeem Is Not a Hero karya Saadia Faruqi. Penelitian ini bertujuan untuk mengkaji bagaimana menghadapi Islamofobia pasca Serangan 9/11 yang digambarkan dalam novel. Penelitian ini menggunakan metode deskriptif kualitatif untuk menganalisis data dan note taking sebagai instrumen penelitian. Penelitian ini direpresentasikan melalui sudut pandang teori strukturalisme genetik tentang bagaimana pengarang sebagai seorang muslim menyampaikan pengalamannya yang terjadi dalam kehidupan pengarang dalam menghadapi islamophobia, penelitian ini menemukan bagaimana tokoh utama berjuang melawan islamophobia dan menggambarkan upaya penanggulangannya hingga diterimanya umat Islam dalam masyarakat social, seperti: menunjukkan sikap dan tindakan moral yang patut diteladani, Memiliki keberanian dalam menghadapi situasi yang menantang sebagai upaya untuk menjelaskan Islam yang sebenarnya, menunjukkan toleransi (moderasi beragama) dan Cinta dan Kasih. Penulis menyuarakan cara-cara tersebut untuk menegaskan kepada masyarakat tentang wajah Islam yang sebenarnya melalui sebuah karya sastra.